Positive effects of probiotics in people living with HIV: a narrative review - Sobocińska, Wiktoria; Kubicka, Gabriela; Kołodyński, Łukasz (Folia Medica Cracoviensia, 2026)
Despite effective antiretroviral therapy (ART), no clear guidelines exist on microbiome-targeted adjuncts for people living with HIV (PLWH). Human immunodeficiency virus (HIV-1) infection damages the gastrointestinal tract by altering the mucosal surface and prompting dysbiosis. Gut microbial imbalance, characterized by the predominance of opportunistic bacteria, leads to increased microbial translocation, which, in turn, results in chronic inflammation, digestive tract symptoms, and reduced quality of life. PLWH have substantial dysbiosis compared to healthy controls. In addition, gastrointestinal complications occur as a side effect of ART treatment. Gut-associated lymphoid tissue (GALT) harbors the majority of CD4+ lymphocytes, and this population is significantly depleted during HIV-1 infection. Antiretroviral therapy does not facilitate CD4+ lymphocyte restoration in GALT tissue. Even if the general CD4+ lymphocyte count increases, the GALT CD4+ count, despite therapy, remains stable and low due to unknown causes. Research assessing probiotics in PLWH on ART has yielded mixed results. Some studies report that probiotics may increase CD4+ T cell counts, improve gut barrier integrity, and reduce the incidence of diarrhea in HIV-positive patients. These benefits may be linked to specific probiotic strains that possibly enhance immune function by promoting regulatory T cell populations, thus decreasing microbial translocation. On the other hand, multiple studies did not show any consistent or significant benefits from probiotic supplementation for PLWH. This article assesses critical clinical trials and systematic reviews on this topic, based on limited existing research data. More data from large clinical trials on this topic is needed to assess whether this is or is not a justified new clinical approach for HIV-1-positive patients.